Manajemen Sarana Dan Prasarana Di MI Qurrota A’yun Sleman - Qiftiyah, Maratul; Sandriansyah, Sandriansyah (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2020)
Madrasas will be able to develop if educational facilities and infrastructure support the learning process. The purpose of this research is to describe the management of facilities and infrastructure in MI Qurrota A'yun. This research is a field research using descriptive method with a qualitative approach. The main subject in this study is the headmaster of the madrasa. Data collection methods used in this research are interviews and observation. Techniques used for data analysis are data reduction, data presentation, and drawing conclusions. Based on the results of the study it can be seen that the management of facilities and infrastructure in MI Qurrota A'yun there are several stages, including: 1) planning of facilities and infrastructure by analyzing the whole beforehand, 2) procurement of facilities and infrastructure, 3) inventory of facilities and infrastructure, 4 ) the use or use of facilities and infrastructure by the madrasa, educators, and all students must be monitored by the selected party madrasa, 5) maintenance of facilities and infrastructure is very important for educators and students so that the goods in the madrasa remain under supervision and care.